Retributive responses - Werner Güth; Hartmut Kliemt; Axel Ockenfels (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Retributive responses do play a role in human behavior. Whether they are primarily triggered by supposed intentions or by observed consequences of actions is an important question. It can be addressed by experimental studies of retributive responses in situations in which the individual actor may inflict harmful consequences without intending and intend harmful consequences without inflicting them. Our experimental results indicate that retributive responses are more strongly influenced by observed consequences than by ascribed intentions. However, individual retributive motivations seem to be overshadowed by concerns that are non-retributive altogether in that they focus on end state distributions independently of who brought them about.
urn:nbn:de:kobv:11-10048712
Keywords: 330